Demografie und Sozialstaat. Arbeitsmarkt hat zentrale Bedeutung - Wöss, Josef; Türk, Erik (Wirtschaft und Gesellschaft, 2014)
Demographic change is one of the key challenges we have to cope with. Adjustments in many areas are required. The impact on welfare states and public pension schemes is mainly addressed by referring to the deterioration of dependency ratios. Unfortunately, in many documents no clear distinction is made between pure demographic and economic issues. Yet, the crucial question is: To what extent the increase of demographic dependency (age group 65+/15-64) will translate into an increase of economic dependency (no. of benefit recipients/no. of contributors). Calculations for EU-27, Austria, Belgium and Poland – based on the “dependency ratio calculator”, a tool developed in the Austrian Chamber of Labor – clearly show: To a high degree, the evolution of the economic dependency ratio will be determined by the evolution of employment. The higher the employment rate, the lower the increase of the economic dependency. The paper proves the validity of the EU-Commission’s statement in the Demography Report 2008: “Raising employment levels [with god jobs] … is arguably the most effective strategy with which countries can prepare for population ageing.”